Strong Convergence on the Aggregate Constraint-Shifting Homotopy Method for Solving General Nonconvex Programming - Zhichuan Zhu; Yeong-Cheng Liou (Journal of Mathematics)
In the paper, the aggregate constraint-shifting homotopy method for solving general nonconvex nonlinear programming is considered. The aggregation is only about inequality constraint functions. Without any cone condition for the constraint functions, the existence and convergence of the globally convergent solution to the K-K-T system are obtained for both feasible and infeasible starting points under much weaker conditions.